Functional and radiological assessment of displaced midshaft clavicle fractures treated through open reduction and internal fixation surgery using pre-contoured locking compression plates - Kakkar, Rohil Singh; Mehta, Deepak; Sisodia, Ankit (International Surgery Journal, 2020)
Background: Fractures of the clavicle constitute approximately 2.6% of all the fractures and nearly 44-66% of fractures around shoulder. Methods: This particular study is intended to assess the functional and radiological outcomes in a series of 32 patients with closed displaced midshaft clavicle fractures treated through open reduction and internal fixation surgery using pre-contoured clavicle locking compression plates. Results: All 32 patients achieved fracture union within 6 months follow up period. As per Constant-Murley scoring, 56.25% cases had excellent results, 34.37% cases had good, 6.25% cases had fair and 3.12% of the cases had poor results respectively. Conclusions: Open reduction and internal fixation surgery with pre-contoured locking compression plates in the displaced midshaft clavicle fractures restores the anatomy, biomechanics and contact loading characteristics of the clavicle and significantly reduces the incidence of non-union with improved functional outcomes resulting in better patient satisfaction.